Young people's attitudes towards integrating physical activity as part of mental health treatment: A cross‐sectional study in youth mental health services. Issue 5 (19th July 2021) - Parker, Alexandra G.; Trott, Emma; Bourke, Matthew; Klepac Pogrmilovic, Bojana; Dadswell, Kara; Craike, Melinda; McLean, Sîan A.; Dash, Sarah; Pascoe, Michaela
Abstract: Introduction: Due to the significant burden associated with mental disorders that have their onset in youth, there is a critical need to improve treatments and treatment outcomes. Given the evidence for physical activity (PA) as an effective intervention for reducing depression and anxiety symptoms in young people, we examined young people's attitudes towards and acceptability of PA as part of mental health treatment, predictors of current engagement in PA and predictors of attitudes towards PA as a treatment option. Methods: Participants in this cross‐sectional study were 88 young people (15–25 years) who were engaged in treatment at youth mental health services in Melbourne, Australia. Results: Young people's attitudes towards PA as a treatment option were generally positive. The acceptance of PA as a treatment option was predicted by fewer perceived barriers and more benefits to exercise, higher autonomous motivation and lower amotivation; whereas, the only significant predictor of current engagement in PA was autonomous motivation. Discussion: The integration of PA interventions within mental health treatment appears to be acceptable to young people; however, acceptance of PA as a treatment option is influenced by perceived barriers and benefits of PA and autonomous motivation. A focus on increasing autonomous motivation by enhancing the perceived value of PA and choosing preference‐based, enjoyable activities may assist in addressing the complex range of factors that impact the ability of these young people to become more physically active. Addressing these factors may assist with implementing PA interventions within psychological treatments for mental disorders.